The medical knowledge of pre-Islamic Arabs as Manifested in Poetry - Almharat, Raed Hamad (Journal of Humanities & Social Sciences, 2021)
The study aims to uncover the components of the medical knowledge of pre-Islamic Arabs as Manifested in Poetry, and the effect of this knowledge in the formation of poetic image, the study adopted the descriptive analytical method, which is concerned with extrapolating the poetic phenomenon and analyzing its dimensions. : The study presented a group of diseases that were illustrated in the pre-Islamic poetry, and talked about the ways adopted by the Arabs in the treatment, and has referred to the most important medical instruments and machines that were used. The treatments took different methods, such as: drugs and combination medicines, herbs and medicinal plants therapy, phylactery therapies, as well as they activate for surgery, cosmetic operations, obstetrics and circumcision surgery. Then the study dealt with the medical knowledge in the formation of poetic image. The study concluded by mentioning the results, including the medical scientific knowledge of the Arabs in the pre-Islamic era was convenient to their level of civilization, guided them through their personal experiences and expertise inherited, or swaging contact civilized their neighboring Nations, as well as their dependence on the magic in the treatment of many diseases. . This medical knowledge has formed a cultural patrimony through poetry. They mentioned a lot of diseases, medicines and medical instruments, and employed it in lots of their poetic images. The researcher recommends submitting poetry to other heritage and historical sources when studying the medical knowledge of pre-Islamic Arabs as, because poetry is the Diwan of the Arab and it is the bowl of their culture. Also, the researcher suggest to Conduct poetry studies dealing with other cultural aspects that aim to provide various aspects of civilization among the pre-Islamic Arabs.